Case Report: Severe psoriasis skin lesions following ofatumumab treatment for multiple sclerosis - Żukowicz-Wyrwa, Wioletta Katarzyna; Markiet, Karolina; Damps, Tatsiana; Ciarka, Aleksandra; Karaszewski, Bartosz; Nowicki, Roman (Frontiers in Immunology, 2025)
The article explores a case study of a patient diagnosed with relapsing-remitting multiple sclerosis (RRMS) who, while receiving treatment with the anti-CD20 monoclonal antibody ofatumumab, developed psoriatic skin lesions. Initially, sharply demarcated, scaly, erythematous lesions were observed only in the anogenital area. After several weeks, additional lesions appeared on the ear lobes, scalp, and lower legs following subsequent administrations of ofatumumab. A comprehensive differential diagnosis of the skin lesions was performed, which included consideration of autoimmune chronic diseases, infectious disease manifestations, and skin carcinomas. Biopsies of the lesions were obtained and underwent histopathological examination. Based on the clinical presentation and further investigations, it was concluded that the skin lesions were an atypical adverse reaction to ofatumumab, manifesting as psoriasis. In addition to presenting this case, we analyze the spectrum of common adverse reactions associated with ofatumumab, as well as the occurrence of psoriasis following other anti-CD20 therapies. To the best of our knowledge, this is a rare, documented instance of psoriasis occurring in a patient receiving ofatumumab for the treatment of multiple sclerosis.